Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages THESE RULES WERE ALTERED AND REVISED ON GENERAL MEETING NIGHT, JAN. 11th, 1908 Committee. F. TAUNTON (Chairman). G. STRADLING. F. ARCHER. G. LYTHGO. H. J. SMITH. J. VAUGHAN. A. CHARTERS. Trustees. Funeral Fund. Sick Fund. J. GORE. A. HALL. E. STRADLING. T. BOURDON. T. H. BOSLEY. J. PINDLEBURY. HENRY HOOKE, Secretary, 58, Nelson Street, St. Peter Street, Hackney Road, N.E. 345/7/2/2